2014
DOI: 10.1590/1414-462x201400010012
|View full text |Cite
|
Sign up to set email alerts
|

Insuficiência renal crônica no Brasil segundo enfoque de causas múltiplas de morte

Abstract: Cad. Saúde Colet., 2014, Rio de Janeiro, 22 (1): 75-85 75 Artigo OriginalResumo Este estudo investiga a mortalidade por doença renal crônica (DRC) por meio das causas múltiplas de morte no Brasil e apresenta a análise de associação entre as causas de óbitos de pacientes em terapia renal substitutiva (TRS), considerando causas associadas de morbimortalidade e características epidemiológicas e sociodemográficas. Utilizou-se a base nacional em TRS centrada no indivíduo para os anos de 2000 a 2004 e a técnica mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
1
12
0
9
Order By: Relevance
“…This particularity is related to the deprivation of food resources, inaccessibility to water networks and above all, difficulties in access to public health services. 24 This is corroborated by a study 25 conducted through the National Database on Renal Replacement Therapy, which revealed a lower proportion of users who started dialysis treatment in the Northeast region. In addition, the authors emphasize that in the Northeast there is a prevalence of deaths caused by dialysis, estimated at 39.2%, in relation to other regions of the country.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…This particularity is related to the deprivation of food resources, inaccessibility to water networks and above all, difficulties in access to public health services. 24 This is corroborated by a study 25 conducted through the National Database on Renal Replacement Therapy, which revealed a lower proportion of users who started dialysis treatment in the Northeast region. In addition, the authors emphasize that in the Northeast there is a prevalence of deaths caused by dialysis, estimated at 39.2%, in relation to other regions of the country.…”
mentioning
confidence: 78%
“…It is inferred, therefore, that these results may reflect the insufficiency of care activities, since most complications were preventable. 25 It is estimated that, worldwide, adverse events in hospital institutions have high rates of magnitude. It is reported that, in Brazil, these indices are in agreement with those found in international studies, however, when dealing with avoidable adverse events, Brazil occupies a prominent position in proportional terms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…the accumulation of nitrogenous products in the bloodstream, such as urea and creatinine that should have been filtered and excreted by the kidneys [1,2]. According to Siviero et al [3], this condition is due to the natural process of population aging and the increasing number of carriers of diabetes mellitus and arterial hypertension, which are the most commonly associated morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…In the Northeast region, there are 134 active and regulated dialysis centers, which correspond to 18% of dialysis units in the country. 18 A study 19 showed that the Northeast region presented a smaller proportion of patients who started treatment. Some factors that contribute to this reality include the low educational level and socioeconomic condition.…”
mentioning
confidence: 99%